2004
DOI: 10.1140/epja/i2003-10237-5
|View full text |Cite
|
Sign up to set email alerts
|

Light clusters in nuclear matter of finite temperature

Abstract: Abstract. We investigate properties and the distribution of light nuclei (A ≤ 4) in symmetric nuclear matter of finite temperature within a microscopic framework. For this purpose we have solved few-body Alt-Grassberger-Sandhas type equations for quasi-nucleons that include self-energy corrections and Pauli blocking in a systematic way. In a statistical model we find a significant influence in the composition of nuclear matter if medium effects are included in the microscopic calculation of nuclei. If multipli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
(53 reference statements)
3
11
0
Order By: Relevance
“…The data provide experimental evidence for a large degree of alpha clustering in this low density matter, in agreement with theoretical predictions [1,7,8,9]. Temperature and density dependent symmetry free energies and symmetry energies have been determined at densities of 0.05ρ 0 or less, where ρ 0 is the ground state density of symmetric nuclear matter, by application of an isoscaling analysis [10,11].…”
supporting
confidence: 77%
“…The data provide experimental evidence for a large degree of alpha clustering in this low density matter, in agreement with theoretical predictions [1,7,8,9]. Temperature and density dependent symmetry free energies and symmetry energies have been determined at densities of 0.05ρ 0 or less, where ρ 0 is the ground state density of symmetric nuclear matter, by application of an isoscaling analysis [10,11].…”
supporting
confidence: 77%
“…Nuclear matter at densities much less than the saturation density tends to form clusters [9][10][11][12][13] to minimize its energy and entropy. As a result two-three-and many-body correlations are formed.…”
Section: Chapter4 Nuclear Statistical Equilibrium (Nse) Modelmentioning
confidence: 99%
“…This creates new bound states (clusters) which appear as new particle species in the system, change its composition and modify its thermodynamical behavior. Studies [10,13] showed that clusters with A= 2, 3 and 4 are dominant at low density and so they must be included in any equation of state that describes the nuclear matter at this limit.…”
Section: Chapter4 Nuclear Statistical Equilibrium (Nse) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The data provide experimental evidence for a large degree of alpha clustering resulting from nucleon coalescence in this low density matter,as predicted by a number of theoretical predictions. [20][21][22][23][24][25] Experimental symmetry free energy coefficients have been derived using the isoscaling method. The isoscaling technique assumes that for two systems with similar temperatures but different N/Z ratios, the ratio of yields of a particular isotope in the two systems may be expressed as where C is a constant.…”
Section: Light Particle Clusterization In Nuclear Matter At Very Low mentioning
confidence: 99%